Analisis Strategi Digital Fundraising Dalam Meningkatkan Jumlah Muzakki (Studi Pada Laz Opsezi Kota Jambi) - Sinta Haryani; Habrianto Habrianto; Nurfitri Martaliah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The fundraising strategy at Lembaga Amil Zakat is a way and effort to influence the community. The purpose of this study is to find out how effective the implementation of digital fundraising strategies is, how digital fundraising strategies are and what are the supporting and inhibiting factors of digital fundraising strategies in increasing the number of muzakki. The method used in this study is qualitative descriptive. The results of this study are known that the effectiveness of the digital fundraising strategy implemented by LAZ OPSEZI has been optimally distributed to mustahik and digital fundraising strategies, namely: Promotion is carried out digitally in order to continue to increase the number of muzakki, such as Q-RIS, Transfer, Zakat Features to facilitate in carrying out Zakat, infak and alms. However, at LAZ OPSEZI muzakki there are still many offline or pick up zakat. One of the supporting factors is the legality of LAZ OPSEZI, and the obstacle is that there are still many who do ZIS offline because they lack understanding in digital form.